The minimal important difference for target lobe volume reduction after endoscopic valve therapy - Gompelmann, Daniela; Kontogianni, Konstantina; Schuhmann, Maren; Eberhardt, Ralf; Heußel, Claus Peter; Herth, Felix (The International journal of chronic obstructive pulmonary disease, 2018)
Objective: Endoscopic valve therapy aims at target lobe volume reduction (TLVR) that is associated with improved lung function, exercise tolerance and quality of life in emphysema patients. So far, a TLVR of >350 mL was considered to be indicative of a positive response to treatment. However, it is not really known what amount of TLVR is crucial following valve implantation. Patients and methods: TLVR, forced expiratory volume in 1 second (FEV1), residual volume (RV) and 6-minute walk distance (6-MWD) were assessed before and 3 months after valve implantation in 119 patients. TLVR was calculated based on computed tomography (CT) scan analysis using imaging software (Apollo; VIDA Diagnostics). Minimal important difference estimates were calculated by anchor-based and distribution-based methods.Results: Patients treated with valves experienced a mean change of 0.11 L in FEV1, -0.51 L in RV, 44 m in 6-MWD and a TLVR of 945 mL. Using a linear regression and receiver operating characteristic analysis based on two of three anchors (ΔFEV1, ΔRV), the estimated minimal important difference for TLVR was between 890 and 1,070 mL (ie, 49%–54% of the baseline TLV). Conclusion: In future, a TLVR between 49% and 54% of the baseline TLV, should be used when interpreting the clinical relevance.